Remittances, migrants' education and immigration policy: Theory and evidence from bilateral data - Frédéric Docquier; Hillel Rapoport; Sara Salomone (Bar-Ilan University, Department of Economics, 2011)
We investigate the relationship between remittances and migrants' education both theoretically and empirically, using original bilateral remittance data. At a theoretical level we lay out a model of remittances interacting migrants' human capital with two dimensions of immigration policy: restrictiveness, and selectivity. The model predicts that the relationship between remittances and migrants' education is ambiguous and depends on the immigration policy conducted at destination. The effect of education is more likely to be positive when the immigration policy is more restrictive and less skill-selective. These predictions are then tested empirically using bilateral remittance and migration data and proxy measures for the restrictiveness and selectivity of immigration policies at destination. The results strongly support the theoretical analysis, suggesting that immigration policies determine the sign and magnitude of the relationship between remittances and migrants' education.
Keywords: F24; F22; O15; J61; 330; Remittances; Migration; Brain Drain; Immigration Policy; Rücküberweisungen; Bildungsniveau; Migranten; Migrationspolitik; Brain Drain; Welt